Application of the NIST 800-86 Framework to Forensic Digital Evidence for Signal and Litmatch - Hapsari, Nurul Puspa; Parga Zen, Bita (Journal of Innovation Information Technology and Application (JINITA), 2024)
Exchanging messages is a routine that cannot be avoided at this time. With the development of technology, exchanging messages has become easier to do. The thing that makes exchanging messages easier is the instant messaging application. Examples of instant messaging applications are the Signal and Litmatch applications. In addition to the ease of exchanging messages, there are also negative impacts, such as threats and bullying. Forensic analysis is carried out to find and obtain evidence of digital crimes. This research was conducted to find and obtain evidence of Signal and Litmatch applications by conducting case scenarios and using the National Institute of Standards and Technology (NIST) 800-86 method. This study uses the MobilEdit Forensic and Autopsy tools to obtain evidence from the Signal and Litmatch applications.